Decreased CD8+ Lymphocytic Infiltration in Multifocal and Multicentric Glioblastomas - Wang, Run; Song, Yifu; Hu, Tianhao; Wang, Xiaoliang; Jiang, Yang; Zhang, Di; Yu, Juanhan; Han, Sheng; Kan, Liang (Frontiers in Oncology, 2021)
Purpose Multifocal and multicentric glioblastomas (mGBMs) are associated with a poorer prognosis compared to unifocal glioblastoma (uGBM). The presence of CD8+ tumor-infiltrating lymphocytes (TILs) is predictive of clinical outcomes in human malignancies. Here, we examined the CD8+ lymphocytic infiltration in mGBMs. Methods The clinical data of 57 consecutive IDH wildtype primary mGBM patients with histopathological diagnoses were retrospectively reviewed. CD8+ TILs were quantitatively evaluated by immunohistochemical staining. The survival function of CD8+ TILs was assessed by Kaplan–Meier analysis and Cox proportional hazard models. Results No significant difference in the concentration of CD8+ TILs was observed among foci from the same patient (P>0.150). The presence of CD8+ TILs was similar between multifocal and multicentric GBMs (P=0.885). The concentration of CD8+ TILs was significantly lower in mGBMs than in uGBMs (P=0.002). In mGBM patients, the CD8+ TIL level was associated with preoperative KPS (P=0.018). The median overall survival (OS) of the 57 mGBMs was 9 months. A low CD8+ TIL level (multivariate HR 4.404, 95% CI 1.954-9.926, P=0.0004) was an independent predictor of poor OS, while postoperative temozolomide chemotherapy (multivariate HR 6.076, 95% CI 2.330-15.842, P=0.0002) was independently associated with prolonged OS in mGBMs. Conclusions Decreased CD8+ TIL levels potentially correlate with unfavorable clinical outcome in mGBMs, suggesting an influence of the local immuno-microenvironment on the progression of mGBMs.